A wide-spectrum mid-infrared electro-optic intensity modulator employing a two-point coupled lithium niobate racetrack resonator - Hyeon Hwang; Kiyoung Ko; Mohamad Reza Nurrahman; Kiwon Moon; Jung Jin Ju; Sang-Wook Han; Hojoong Jung; Min-Kyo Seo; Hansuek Lee (APL Photonics)
Optical intensity modulators (OIMs) are essential for mid-infrared (mid-IR) photonics, enabling applications such as bond-selective molecular sensing, and free-space communications via atmospheric windows. Integrated photonics offers a compact and cost-effective solution, yet on-chip mid-IR OIMs significantly underperform compared to their near-IR counterparts. Furthermore, despite the potential benefits for system reconfiguration in accessing various communication frequencies and molecular absorption bands, developing a single OIM capable of operating across a broad spectral range remains a challenge. In this study, we introduce an on-chip OIM that operates over a wide wavelength range in the mid-IR, implemented using a racetrack resonator structure in thin film lithium niobate (TFLN). The modulator employs a two-point coupling scheme, allowing active control of the coupling strength to maintain critical coupling and thereby ensuring high modulation extinction across a wide spectral region. This approach not only achieves high modulation performance but also relaxes the design constraints and fabrication precision typically associated with resonator-based modulators, as confirmed through an analytic model. Implemented in TFLN having a wide transmission spectrum and strong electro-optic coefficient, the OIM demonstrates a modulation extinction ratio exceeding 20 dB with an electro-optic efficiency of 7.7 V cm over the wavelength range of 3.3–3.8 μm, which falls within the first atmospheric transmission widow in the mid-IR. This approach can be adapted to other spectral regions, providing a versatile solution for diverse photonic applications.